2011
DOI: 10.1371/journal.pone.0025752
|View full text |Cite
|
Sign up to set email alerts
|

Xanthene Food Dye, as a Modulator of Alzheimer's Disease Amyloid-beta Peptide Aggregation and the Associated Impaired Neuronal Cell Function

Abstract: BackgroundAlzheimer's disease (AD) is the most common form of dementia. AD is a degenerative brain disorder that causes problems with memory, thinking and behavior. It has been suggested that aggregation of amyloid-beta peptide (Aβ) is closely linked to the development of AD pathology. In the search for safe, effective modulators, we evaluated the modulating capabilities of erythrosine B (ER), a Food and Drug Administration (FDA)-approved red food dye, on Aβ aggregation and Aβ-associated impaired neuronal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 45 publications
4
62
0
Order By: Relevance
“…Two ERs were employed to investigate the possible inhibition mechanism induced by multiple ERs. In a previous study, various concentrations of ER were investigated based on the molar ratio between ER and Aβ40 monomeric strands; two ERs bound to one Aβ40 [7]. Thus, preparation of two ERs with one Aβ40 in one system is a feasible configuration, even though it may not be common considering the experimental conditions in terms of concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two ERs were employed to investigate the possible inhibition mechanism induced by multiple ERs. In a previous study, various concentrations of ER were investigated based on the molar ratio between ER and Aβ40 monomeric strands; two ERs bound to one Aβ40 [7]. Thus, preparation of two ERs with one Aβ40 in one system is a feasible configuration, even though it may not be common considering the experimental conditions in terms of concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Erythrosine B has been implicated as a novel drug candidate to hinder Aβ peptide aggregation [6][7][8]. ER is a common xanthene dye that has been approved by the Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature [23e26], halogenation of aromatic molecules significantly affects aromatic interactionmediated self-assembly processes, including Ab aggregation and cytotoxicity. For example, Wong and Kwon reported that erythrosine B, a xanthene dye, can modulate Ab 40 aggregation [27]. Note that competitive interaction between aromatic residues is attributed to the formation of b-sheet rich Аb structures [28].…”
Section: Screening Of Xanthene Dyes Under Dark For Inhibition Of Ab Amentioning
confidence: 99%